1985
DOI: 10.1148/radiology.156.2.2989975
|View full text |Cite
|
Sign up to set email alerts
|

Scrotal calculi: sonographic detection.

Abstract: Scrotal calculi are freely moving concretions that lie in the space between the tunicae lining the scrotum and the testicles. They are believed to originate either as fibrinous deposits in the tunica vaginalis testis or as remnants of the appendix testis or appendix epididymidis that have undergone torsion and become freely movable. A sector real-time scanner with a 7.5-MHz transducer and a small-parts scanner with a 10-MHz transducer were used to visualize scrotal calculi in two patients. The ultrasonic appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 0 publications
0
55
0
1
Order By: Relevance
“…Highfrequency (7.5 to 15 MHz) US is the ideal method for the diagnosis of these calculi, because it offers increased resolution of the scrotal contents (3,4). During an US examination, the calculi are easily defined as round or ovoid due to the hyperechoic nature of the calcification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highfrequency (7.5 to 15 MHz) US is the ideal method for the diagnosis of these calculi, because it offers increased resolution of the scrotal contents (3,4). During an US examination, the calculi are easily defined as round or ovoid due to the hyperechoic nature of the calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, repeated microtrauma may be a risk factor for the development of scrotal calculi (6,7). Histologically, the scrotal calculi consist of fibrinoid deposits around a central nidus of hydroxyapatite (3,8). Biochemical analyses of the calculi have revealed that they are composed of calcium, oxalate and phosphorus (9).…”
Section: Discussionmentioning
confidence: 99%
“…They may result from torsion of the appendix testes or appendix epididymis, or may represent inflammatory deposits that have formed along and separated from the tunica vaginalis. 53,54 On sonography they appear as mobile, echogenic foci with posterior acoustic shadowing (Fig. 29).…”
Section: Paratesticular Massesmentioning
confidence: 99%
“…Such calcifications are believed to result from either torsion of the appendix testis, from inflammation of the tunica vaginalis testis, or from hematomas. 26,27 According to Horstmann, scrotoliths are calcified bodies without clinical importance. 28 However, intratesticular macrocalcifications may also raise the suspicion of large-cell calcifying Sertoli cell tumors, burned-out germ cell tumors, or, like in this case, posttraumatic changes.…”
Section: Discussionmentioning
confidence: 99%